Urban Growth and Land Artificialization in Secondary African Cities: A Spatiotemporal Analysis of Ho (Ghana) and Kpalimé (Togo) - Tchakouni Sondou; Kouassi Rodolphe Anoumou; Coffi Cyprien Aholou; Jérôme Chenal; Vitor Pessoa Colombo (Urban Science)
While many studies have used Earth observations to quantify urbanization in Africa, there is still a lack of empirical evidence on the role of secondary cities in the fastest urbanizing region in the world. Moreover, the diversity of urbanization processes in Africa, which can be more or less compact in terms of land consumption, remains insufficiently acknowledged and under-documented. This empirical study employed mixed methods to address these research gaps. We analyzed and compared the spatiotemporal dynamics of two secondary African cities, Ho (Ghana) and Kpalimé (Togo), between 1985 and 2020. We compared their spatial growth (the rate of urbanization of land) with their respective population growth rates using Landsat TM and ETM+ imagery, and population data. To understand the factors behind eventual differences between the spatial patterns of urbanization of the two cities, our quantitative analysis based on remote sensing was confronted with qualitative data from individual interviews with key stakeholders. Our results showed two distinct urbanization trajectories between 1985 and 2010, with Ho following a more compact pattern than Kpalimé. Since 2010, however, both cities have tended towards urban sprawl, with an urbanization rate greater than the population growth rate. According to the interviews, the main determinants of urban sprawl in these two secondary cities were the absence of housing policies for low-income groups, the absence or inefficacy of urban master plans, the preponderance of single-family housing, and land speculation.